Implementing the Module and Learning Video in Turning Tapered to Enhance the Students’ Competency in Mechanical Engineering Education - Asri, Sarwi; Wu, Ting Ting; Nasrullah Kamal, Muhammad Fariz (Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
The rapid advancements in technology and the demands of Industry 4.0 have underscored the need for innovative teaching approaches in Technical and Vocational Education and Training (TVET) to enhance students’ practical competencies. This study evaluates the effectiveness of module-based and video learning in improving students’ competencies in tapered turning within a lathe machining practice course. Employing a quasi-experimental design, the study involved 41 students from a Mechanical Engineering Education program, divided into an experimental group (19 students) and a control group (22 students). The experimental group used module-based and video learning tools, while the control group relied on traditional teaching methods. The findings revealed a statistically significant improvement in the experimental group’s post-test scores compared to the control group (ð‘¡ = 8.59, ð‘ < 0.05), with a mean difference of 14.467. The experimental group also achieved an average normalized gain (N-Gain) score of 0.7063, categorized as "high," indicating a substantial improvement in learning outcomes. The study demonstrates that the integration of module-based and video learning enhances both cognitive understanding and practical skills, making the learning process more interactive, accessible, and aligned with industry needs. These findings highlight the potential of multimedia-based teaching tools to bridge the gap between traditional methods and modern educational requirements, contributing to the development of industry-ready graduates in the era of Industry 4.0.